Technical Solution for Processing of Flax Raw Materials - Berezovsky, Yu.V. (Science and Innovation, 2024)
Theory and practice of technical upgrade of factories processing flax raw material, modernization of production, the application of advanced technologies and equipment have been discussed. The results of simulation of cleaning of flax fibers from non-fibrous impurities have been analyzed for various options and configurations of equipment. The possibility and expedience of application of innovative solutions for improving physical and mechanical properties and quality of flax raw material have been proved. The conditions for development of the processing industry in Ukraine and achieving of positive results from processing of stem flax material using innovative processing technologies, advanced technical solutions, and original methods of processing by new equipment have been described.